Transition metal (X = Mn, Fe, Co, Ni, Cu, Zn)-doped graphene as gas sensor for CO2 and NO2 detection: a molecular modeling framework by DFT perspective - Mollaamin, Fatemeh; Monajjemi, Majid (Springer Science and Business Media LLC, 2023)
In this research, CO2 and NO2 adsorption on doped nanographene (NG) sheets with transition metals (Fe, Ni, Zn) and (Mn, Co, Cu), respectively, have been applied for scavenging of these toxic gases as the environmental pollutants. The values of changes of atomic charge density have illustrated a more significant charge transfer for Ni-doped C-NG through CO2 adsorption and a more remarkable charge transfer for Co-doped C-NG through NO2 adsorption. The data of NMR spectroscopy has depicted several fluctuations around the graph of Zn-doped on the nanographene surface. The thermodynamic results from IR spectroscopy have indicated that [Formula: see text] values are almost similar for doped metal transitions of Mn, Co, and Cu on the C-NG nanosheet, while [Formula: see text] has the largest gap of Gibbs free energy adsorption with dipole moment.The Langmuir adsorption model with a three-layered ONIOM using CAM-B3LYP functional accompanying LANL2DZ, EPR-III and 6-31 + G (d,p) basis sets due to Gaussian 16 revision C.01 program on the complexes of CO2 → (Fe, Ni, Zn) and NO2 → (Mn, Co, Cu) doped on the C-NG has been accomplished. Then, NMR and IR spectroscopy, nuclear quadrupole resonance, and natural bond orbital analysis have been accomplished for evaluating chemical shielding tensors, thermodynamic properties, electric potential, and occupancy fluctuation through bond orbitals, respectively. In addition, frontier orbitals of LUMO, HOMO, and also a series of chemical reactivity parameters have been calculated. Finally, time-dependent-DFT method due to UV-VIS spectrums has been accomplished to discern the low-lying excited states of CO2 and NO2 adsorption on the (Fe, Ni, Zn) and (Mn, Co, Cu), respectively, doped C-NG sheet.